Peningkatan Hasil Belajar Peserta Didik melalui Metode Problem Solving dalam Pelajaran Matematika Kelas IV SDN 12 Nan Sabaris - Zulmaini Zulmaini (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
Indonesian society progress and communication technology very rapidly. Therefore, it needs qualified human resources. Forming qualified human resources that can be done through formal education. In fact a lot of students who are less able to get a satisfactory learning outcomes. Therefore in inidicobakan research using methods Problem Solving in mathematics in grade IV SDN 12 Nan ​​Sabaris. The formulation of this research is how the result of learning mathematics in grade IV SDN 12 Nan ​​Sabaris Padang Pariaman using methods of problem solving? This study uses a classroom action research with two cycles. The survey results revealed that students' mathematics learning outcomes increased from the first cycle to the second cycle. This proves that the method of problem solving can improve students' mathematics learning outcomes.